Hybrid between Genetic Algorithm and Artificial Bee Colony for Key Generation Purpose - Taher, Ali AbdulKadhim; Kadhimb, Suhad Malalla (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2019)
Cryptography is a significant tool for guarantee a protected and secured data. In asymmetric key algorithms, the key generation plays an important role for applied the security. This research focus on enhance genetic algorithm's population by using artificial bee colony to generate keys that are unique and random. The five statistical tests ( Frequency test (monobit test), Serial test (two-bit test), Poker test, runs test and autocorrelation test) are used to compute the fitness. The programming language Pythom3 was used in programming the proposed method. The proposed algorithm is acquired higher quality solutions within a reasonable computational time compared to traditional genetic algorithm.